MODELING OF HR-PROCESSES IN THE IMPLEMENTATION OF THE PERSONNEL MANAGEMENT POLICY OF THE ENTERPRISE (Development Service Industry Management, 2024)
Modern enterprises need to make effective HR decisions that allow them to achieve competitive advantages in the market and maintain their current level of development. In order to make such decisions, it is necessary to effectively organize all HR processes that are interconnected and mutually influenced. Personnel processes are directly related to the formation of the enterprise's personnel policy  directions of its implementation determine the quality and features of personnel decisions. The relevance of the study is due to the need to model HR processes, which allows for a better understanding of the complex interrelationships between them, as well as to predict the results and consequences. The article notes that in modern management practice, it is increasingly difficult to determine the list and conditions for the implementation of personnel processes at enterprises. This is due to their diversity, the use of new technologies and the growing role of HR management in building the overall strategy of enterprises. It is noted that the modeling of HR processes is a powerful tool in creating an effective organization, which allows solving not only current problems, but also predicting future challenges and preparing for them. Thanks to modeling, companies can secure a competitive advantage and achieve sustainable development.The Garvard HR model framework is proposed for adaptation and implementation in the national HR practice. Modeling by HR specialists of personnel processes at the enterprise will contribute to their optimization and automation, forecasting the consequences of the impact of new HR technologies dictated by changes taking place in the personnel policy and, in general, increasing the efficiency of enterprises. The stages of the process of modeling HR processes in HR management are formed, with their characteristic features, as well as a mathematical description of the dependence of staff performance on the level of institutional measures of influence. It is noted that the productivity of personnel directly depends on degree of their loyalty to the enterprise, level of competence, degree compliance of professional training with working conditions and psychological climate. The scientific publication further develops the use of correlation models for modeling HR processes through the implementation of an effective HR policy of an enterprise.
Keywords: personnel policy; HR processes; HR modeling; correlation and regression analysis